MODIFIED NUMERICAL TABLES FOR THE CALCULATION OF NON-SPHERICAL CONTRIBUTION TO SECOND VIRIAL COEFFICIENTS AND THE CORRELATION EQUATIONS OF STATE FOR CO,, CS, AND C6H6 (Journal of Sciences, Islamic Republic of Iran)
A revised analysis of the effect of long-range nonspherical terms in the intermolecular potential on the second virial coefficient is presented with a preferred Hartree-Fock-Dispersion functional (HFD-C) spherical core treatment of the integrations for small intermolecular distances. A set of modified numerical tables for the accurate calculation of the nonspherical contribution to the second virial coefficients is presented and a new correlation equation of B~O for C02, CS2 and C6H6 is reported